Relações de gênero em escolas do município de Getúlio Vargas, RS, 1990-2020 - Bruneto, Eliane Salete (2022)
The dissertation addresses the history of gender relations in the school environment in the city of Getúlio Vargas (RS), from 1990 to 2020. It formulates the problem of research with a question, that is: how were the gender relations developed, historically, in the schools of Getúlio Vargas in this period? Its main objective is to research how these relationships occurred in schools in the municipality. The firstof the schools surveyed is public, part of the municipal network; the second is also public, but from the state network and the third is a special education school. The dissertation also investigates how these relationships contributed to the maintenance of socially established order and male power. The research is based on the theoretical and conceptual references of Social History and dialogues with the history of education and with academic publications on the history of women and the feminist movement in Brazil. Topics such as educational policies, women's rights, educational legislation, gender relations, history teaching, power relations and the role of the school in society. The research sources are of two types: school documents, especially the minutes books and the record books of occurrences, which allow to know the relationships established between people of different genders in the school environment and the oral testimonies of teachers, principals, coordinators pedagogical and parents who lived the period selected for the research. The interpretation of written documentsfollows the methodology of discourse analysis, while oral testimonies were collected and interpreted according to the methodology of Oral History. It concludes that gender relations inthe three schools studied reproduced the general context, as they were marked by behaviors, discourses.